The coronal pulp cavity index: A forensic tool for age determination in adults - Swati Shrikant Gotmare; Tanmik Shah; Treville Periera; Mandavi S Waghmare; Subraj Shetty; Sushama Sonawane; Maina Gite (Wolters Kluwer Medknow Publications, 2019)
Background: Various biochemical and histological methods are available for human age determination which are invasive and may require extraction of teeth. The present study aims to assess the accuracy of age estimation from tooth-coronal index (TCI) of known age and sex individuals and to present a noninvasive method for age estimation. Materials and Methods: This retrospective study comprised 88 patients, which included 54 males and 34 females. An orthopantomogram of these individuals were taken, and premolars and molars in the same were evaluated. The height of the crown (coronal height [CH]) and the height of the coronal pulp cavity (coronal pulp cavity height [CPCH]) was digitally measured on the computer screen. The TCI given by Ikeda et al. in 1985 (TCI = [CPCH × 100]/CH.) was computed on each tooth and regressed on real age of the sample. The mean, median, range, and standard deviation of the computed index were calculated. The correlation between the actual age and the estimated age was calculated using t-test. P < 0.05 was considered significant. Results: Results revealed that there is a significant correlation between the TCI with age. Increase in TCI observed with age; however, it showed no significant sex difference. Conclusion: TCI is a precise, noninvasive and easily used reliable biomarker for age estimation and is applicable to both living and dead individuals.